Virtual labs [electronic resource] (MERLOT, 2020)
Quoted from the homepage: Open Educational Practices and Virtual Labs: Redesigning STEM laboratory courses with virtual labs (open or not) is becoming an emerging requirement. Openly sharing educational practices with virtual labs could accelerate the scaling of the effective adoption of virtual labs. MERLOT's Virtual Labs portal provides guidance and collections of OER and non-OER virtual labs for you to explore. Check out SkillsCommons' collection of augmented reality OER healthcare scenarios too. Explore the collection of over 50 open teaching ePortfolies by faculty who adopted virtual labs, participated in learning communities, and captured their plans, implementations, and assessments of the student learning outcomes. The faculty also video recorded their reflections on their redesign of their lab courses as part of the open educational practice.